Disc-loaded monopole array for switched beam control - Kamarudin, Muhammad Ramlee; Hall, P. S. (Institution of Engineering and Technology, 2002)
Switched beam control is demonstrated using a disc-loaded monopole antenna on a finite ground plane with four parasitic elements. The beam direction can be switched by open circuiting one of the parasites. The array antenna gives a gain of 5.1 dBi at 2.45 GHz, which is more than three times that of a single element. The input return loss bandwidth is 24% and the radiated beam is elevated above the ground plane by about 500. The measured results show good agreement with simulations